Bio-Synthesized Zinc Oxide Nanoparticles Using Plant Extracts - Mohammad, Ahmad Zulfaqar; Ainuddin@Nordin, Ainun Rahmahwati (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In this day and age, nanoparticles have become one of the essential needs of society in various sectors such as development. Another applications have the potential to be used with ZnO, therefore the development can improve the quality of nanoparticles to make them more specific. Synthesis procedures should avoid the use of harmful chemicals to ensure that the environment is maintained. The green biosynthesis method is a simple procedure where the plants used are easy to find and where the methods used are safe. In this paper, a brief overview of the Zinc Oxide Nanoparticle (ZnO) method is used to identify the shape, size and characteristics found in plant extract such as coriander, brinjal and banana peel. The unresponsive effect of temperature on ZnO during the experiment can change the size, shape and characteristics. To determine the characteristics of the ZnO synthesis from plant extract, machines such as XRD, FESEM and UV-Vis were used in this experiment.